Transmission Frequencies of Introgressed Festuca pratensis Chromosomes and Chromosome Segments in Lolium perenne. Issue 5 (1st September 2013) - King, Julie; Armstead, Ian; Harper, John; King, Ian
ABSTRACT: The introgression of genetic variation from related species into crops provides an important route by which superior plant varieties can be produced. The primary aim of introgression involves the transfer of a small chromosome segment from a related species into a chromosome of a crop species (via recombination at meiosis) to generate an interspecific recombinant chromosome. Very little is known about the selective pressures that act on the products of interspecific recombination. Seven monosomic substitution lines were developed between Lolium perenne and Festuca pratensis . When each line was backcrossed to L. perenne recombination occurred between the F. pratensis chromosome and its L. perenne homoeologue, resulting in backcross populations carrying L. perenne/F. pratensis recombinant chromosomes. This paper describes the relationship between the frequency of generation of interspecific recombinant chromosomes with the frequency of their transmission to the next generation. The results reveal the presence of neutral, negative, and positive selection pressures for the transmission of F. pratensis chromosomes and L. perenne/F. pratensis recombinant chromosomes through the gametes to the next generation. The type of selection pressure observed depended on which linkage group the F. pratensis chromosome under study was derived from. The implications of these results are discussed.